Nasal anatomy for the dermatological surgeon. (1st September 2014) - Oliphant, T.J.; Langtry, J.A.A.
Summary: The nose is an important site of skin pathology and skin cancer in particular, underlining the importance of the nose to the practice of dermatology. This article is intended to serve as an overview of the anatomy of the nose for dermatologists and dermatological surgeons. Areas of clinical relevance are emphasized with examples.